Genome-wide analyses identify a role for SLC17A4 and AADAT in thyroid hormone regulation - Alexander Teumer (Nature Portfolio, 2018)
Thyroid dysfunction is a common public health problem and associated with cardiovascular co-morbidities. Here, the authors carry out genome-wide meta-analysis for thyroid hormone (TH) levels, hyper- and hypothyroidism and identify SLC17A4 as a TH transporter and AADAT as a TH metabolizing enzyme.